Executive Functions Profile in Extreme Eating/Weight Conditions: From Anorexia Nervosa to Obesity - Fagundo, Ana B.; de la Torre, Rafael; Jiménez-Murcia, Susana; Agüera, Zaida; Granero, Roser; Tárrega, Salomé; Botella, Cristina; Baños, Rosa; Fernández-Real, Jose M.; Rodríguez, Roser; Forcano, Laura; Frühbeck, Gema; et al. (PloS one, 2012)
Extreme weight conditions (EWC) groups along a continuum may share some biological risk factors and intermediate neurocognitive phenotypes. A core cognitive trait in EWC appears to be executive dysfunction, with a focus on decision making, response inhibition and cognitive flexibility. Differences between individuals in these areas are likely to contribute to the differences in vulnerability to EWC. The aim of the study was to investigate whether there is a common pattern of executive dysfunction in EWC while comparing anorexia nervosa patients (AN), obese subjects (OB) and healthy eating/weight controls (HC). Thirty five AN patients, fifty two OB and one hundred thirty seven HC were compared using the Wisconsin Card Sorting Test (WCST); Stroop Color and Word Test (SCWT); and Iowa Gambling Task (IGT). All participants were female, aged between 18 and 60 years. There was a significant difference in IGT score (F(1.79); p<.001), with AN and OB groups showing the poorest performance compared to HC. On the WCST, AN and OB made significantly more errors than controls (F(25.73); p<.001), and had significantly fewer correct responses (F(2.71); p<.001). Post hoc analysis revealed that the two clinical groups were not significantly different from each other. Finally, OB showed a significant reduced performance in the inhibition response measured with the Stroop test (F(5.11); p<.001) compared with both AN and HC. These findings suggest that EWC subjects (namely AN and OB) have similar dysfunctional executive profile that may play a role in the development and maintenance of such disorders.